Effect of Aerobic Exercise on White Matter Tract Microstructure in Young and Middle-Aged Healthy Adults - Predovan, David; Gazes, Yunglin; Lee, Seonjoo; Li, Peipei; Sloan, Richard P.; Stern, Yaakov (Frontiers in Human Neuroscience, 2021)
Recent evidence suggests that being physically active can mitigate age-related white matter (WM) changes. In a randomized clinical trial, the effect of 6-month aerobic exercise (AE) or stretching/toning interventions on measures of WM microstructure (WMM) was assessed in a sample of 74 adults aged 20–67 years. Major WM pathways were reconstructed. No significant group-level change in WM tract microstructure following an AE training was observed. Without adjustment for multiple comparisons, an increase in fractional anisotropy (FA) and a decrease in mean diffusivity (MD) of the uncinate fasciculus were observed post-intervention in the AE group in comparison to the stretching group. In the AE group, a significant increase in cardiorespiratory fitness was measured, but did not correlate with FA and MD change. The present results of this study are in accordance with similar studies in healthy adults that did not show significant benefit on WMM after participating in an AE program.